Prolonged Survival on PARP Inhibitor Therapy In a Patient With Stage IV Non-small Cell Lung Cancer: A Case Report - Herrera, Ana Lucía González; MD, Mustafa Al Gburi; MD, Ahmed Ayad; MD, Julio Peguero (Archives of Clinical and Medical Case Reports, 2019)
A BRCA1 mutation has been identified in a 56-year old female with adenocarcinoma of the lung. Following partial response with Nivolumab therapy, the patient started maintenance therapy with Olaparib, a PolyADP-ribose Polymerase (PARP) inhibitor showing sustained progression free response that is still ongoing.